EFFECTS OF NUTRITIONAL STATUS AND NUTRITIONAL INTERVENTION WITH WHEY PROTEIN ON CARDIOVASCULAR HEMODYNAMIC RESPONSE IN PATIENTS WITH SEVERE COPD (CIPEEX, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory condition characterized by chronic airflow obstruction and is associated with cardiocirculatory complications such as pulmonary hypertension and right ventricular dysfunction, which can lead to heart failure. The prevalence of COPD in Brazil is significant, and there is an urgent need for non-pharmacological strategies to improve disease management.Nutrition plays a crucial role in the treatment of patients with severe COPD, particularly in preserving muscle mass and improving lung function. Protein supplementation, especially with Whey Protein, has shown potential in enhancing quality of life and cardiovascular function in these patients. This study aims to evaluate the relationship between nutritional status and cardiovascular changes in patients with severe COPD and to examine the effects of protein supplementation on modulating inflammatory responses.Patients will be recruited and classified according to the severity of COPD and will undergo supplementation protocols as well as hemodynamic and nutritional assessments. The analysis will include the evaluation of inflammatory cytokines and growth factors, aiming to verify the effectiveness of Whey Protein in treating cardiovascular complications associated with severe COPD. If successful, the study could open a new market for the use of Whey Protein in COPD management.
Keywords: chronic obstructive pulmonary disease (copd); protein supplementation; cardiovascular hemodynamics; inflammatory response